Body composition by dual-energy X-ray spectrometry and bioelectrical impedance spectroscopy in a healthy population at age 75 and 80 - Mehlig, K.; Freyer, E.; Tognon, G.; Malmros, V.; Lissner, L.; Bosaeus, I. (Clinical nutrition (Edinburgh, Scotland), 2015)
Bioelectrical impedance spectroscopy (BIS) is a versatile field tool to obtain information about body composition (BC), if prediction equations are available that are valid for the group under consideration. We aimed to validate prediction equations for total body skeletal muscle mass (TBSMM) developed in healthy 75-year olds from the Gothenburg area (Sweden) in a similar sample examined at age 80. We give new prediction equations for fat mass (FM), fat-free mass (FFM), and TBSMM that are based on the entire group of elderly subjects, using values from Dual-energy X-ray spectrometry (DXA) as reference standard. Finally, we describe the longitudinal change in BC in the subset of subjects, who participated at both age 75 and 80. Body composition was measured by DXA and multiple-frequency BIS at age 75 (n = 111) and 80 (n = 91) years. Ordinary and mixed linear regression was used to examine previous and new prediction equations. Longitudinal change was assessed by paired sample t-test. The prediction equations for TBSMM developed in 75-year old subjects showed good validity when applied to the sample of 80 year olds. The results were independent of the presence of a metal prosthesis in hip or knee. New, sex-specific prediction equations for FM, FFM, and TBSMM were derived for 75 – 80 year-old subjects that further improved the accuracy of prediction. Using DXA-derived BC at ages 75 and 80, we observed a decline in TBSMM in both sexes, which was mainly due to muscle loss in the legs. In men, the decrease in trunk FFM was accompanied by an increase in FM, leaving no overall weight change in the trunk. When the 5-year change in TBSMM was based on longitudinal BIS measurements, the results from DXA were reproduced only when the prediction was based on BIS-values at 50 kHz. Good cross-sectional validity of BIS equations for TBSMM was found in a population sample of 80-year olds. The presence of a metal prosthesis did not influence the quality of prediction. New prediction equations for FM, FFM, and TBSMM need to be evaluated in an independent sample.